2017
DOI: 10.1097/jom.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Occupational Injuries on Nonworkers’ Compensation Medical Costs of Patient-Care Workers

Abstract: Objective To estimate the extent to which work-related injuries contribute to medical expenditures paid for by group health insurance. Methods Administrative data on OSHA recordable injuries spanning 2010–2013 were obtained for female patient care workers (n=2,495). Expenditures were aggregated group health insurance claims for 3 and 6 month periods before/after injury. Group health insurance plan type, age group, and job category were control variables. Results Being injured is associated with the odds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…This flow diagram depicts insurance coverage and gaps for both direct health care costs and work disability-related wage replacement for occupational injury/illness. Importantly, while employer-provided or individual-purchased HI may cover health care costs incurred by insured workers related to occupational injury/illness that was not reported to or not covered by WC (Lipscomb, Dement, Silverstein, Cameron, et al, 2009; Williams et al, 2017), HI does not cover time lost from work due to the injury (time-loss). In the flow diagram, HI includes both employer-provided and individual-purchased coverage.…”
Section: Flow Diagram and Analytical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This flow diagram depicts insurance coverage and gaps for both direct health care costs and work disability-related wage replacement for occupational injury/illness. Importantly, while employer-provided or individual-purchased HI may cover health care costs incurred by insured workers related to occupational injury/illness that was not reported to or not covered by WC (Lipscomb, Dement, Silverstein, Cameron, et al, 2009; Williams et al, 2017), HI does not cover time lost from work due to the injury (time-loss). In the flow diagram, HI includes both employer-provided and individual-purchased coverage.…”
Section: Flow Diagram and Analytical Literature Reviewmentioning
confidence: 99%
“…Multiple long-term studies of unionized Washington State carpenters and drywallers have found evidence of cost-shifting from WC to HI for back, upper extremity, and knee disorders (Lipscomb, Dement, Silverstein, Cameron, et al, 2009; Lipscomb et al, 2015; Schoenfisch et al, 2014). Several studies have found associations between occupational injury and subsequent increases in HI expenditures (Asfaw, Rosa, & Mao, 2013; Williams et al, 2017). Expanded HI coverage (via the Affordable Care Act [ACA] or Massachusetts health care reform) was associated with 5% to 10% decreases in hospital and emergency department WC billing volume (Armour, Goutam, & Heaton, 2016; Bronchetti & McInerney, 2017; Heaton, 2012), and conversely, a 10 percentage point decrease in HI coverage was associated with a 15% increase in Texas WC bills (Dillender, 2015), suggesting that broader access to HI may lower WC costs via cost-shifting mechanisms.…”
Section: Research On Coverage Gaps and Cost-shiftingmentioning
confidence: 99%
“…The average outpatient expenditure spent on treatment was 63 % higher for injured workers, which amounted to an extra $10.7 million (2018 dollars) spent in 2005. In a study of patient care workers, Williams et al (2017) found the likelihood of future medical expenditures were higher in workers who had previously experienced a hospital-recorded occupational injury. Table 2 of Waehrer et al (2004).…”
Section: Economic Burden Of Occupational Injuries and Illnesses: All mentioning
confidence: 99%
“…Occupational injuries can affect workers' lives and may cause a substantial economic burden to employees, employers, and society ( 3 , 4 ). In terms of economic impact, it affects the organizational performance such as the indirect costs of the workplace to the employer and employees, especially on the workers' compensation for lost earnings, and medical and rehabilitation expenses ( 5 ). Nurul Ayuni et al in their study concluded that the effects of occupational accidents include loss of ability to work which may affect individual or family income and alteration of living standard.…”
Section: Introductionmentioning
confidence: 99%